Business Ethics and Jesuit Pedagogy. A critical reflection - Carl Antonius Lemke Duque (FahrenHouse, 2018)
Since the end of the 1970s business ethics has become an emerging academic discipline as well as in the US as in Europe pushed particulary by enviromental disasters and business scandals such as, for instance, the case of Exxon Valdez in 1989 or more recently the strategic fraud by the german global automobile brand Volkswagen. The present study deepens into the origins and the current stage of development of Business Ethics focusing on fundamental positions and leading arguments in jesuit business education. The analisis realized in the present study is divided into three parts: (A) A general outline of the development of modern Business Ethic in jesuit pedagogy in Spain. Here, the paper studies the most important contributions shaping deontological ethics by Jesuit authors since the 1960s as well as the most important influences to date, including aspects of the debate on a practical ethic that follows Kantian traditions. (B) Some recent contributions to Business Ethic in jesuit pedagogy in the US. This part focuses on proposals that have been developed to redefine the distinctive aspects of Business Ethics in Jesuit education. These tendencies provide an approach and a possible dialogue with modern, discursive ethics. Finally, (C) a summary and critical reflection of jesuit profile in Business Ethic.